PERAN MAKRO EKONOMI DALAM MEMODERASI VARIABEL FUNDAMENTAL TERHADAP HARGA SAHAM PADA SEKTOR PERINDUSTRIAN (Studi Pada Perusahaan Sektor Perindustrian Yang Tergabung Di Bei Tahun 2020-2023) - Fitria, Ainun; Endah Purnamasari, Puji (AKUNTANSI DEWANTARA, 2025)
This study aims to determine the effect of fundamental variables on stock prices. This type of research uses descriptive quantitative research with the population in the study using companies listed on the Indonesia Stock Exchange in 2020-2023. The sampling of this study used purposive sampling technique by obtaining 116 samples, while the data collection technique used a representative sample of the population. The data analysis technique also uses multiple linear regression analysis.The conclusion from the research results explains that ROA, EPS, PER and DPR have no effect on stock prices. While inflation has an impact on stock prices.